2015
DOI: 10.1200/jco.2015.63.9518
|View full text |Cite
|
Sign up to set email alerts
|

Combined Microsatellite Instability, MLH1 Methylation Analysis, and Immunohistochemistry for Lynch Syndrome Screening in Endometrial Cancers From GOG210: An NRG Oncology and Gynecologic Oncology Group Study

Abstract: PurposeThe best screening practice for Lynch syndrome (LS) in endometrial cancer (EC) remains unknown. We sought to determine whether tumor microsatellite instability (MSI) typing along with immunohistochemistry (IHC) and MLH1 methylation analysis can help identify women with LS.Patients and MethodsECs from GOG210 patients were assessed for MSI, MLH1 methylation, and mismatch repair (MMR) protein expression. Each tumor was classified as having normal MMR, defective MMR associated with MLH1 methylation, or prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
162
0
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 176 publications
(173 citation statements)
references
References 35 publications
5
162
0
6
Order By: Relevance
“…However, our findings do not address the overall utility of screening EIN cases for LS, and, to date, there is no evidence that screening EIN for LS would be fruitfulindeed the field at large has yet to formally agree on universal screening for LS in ECs. [14][15][16][17][18][19][20] Furthermore, LS screening studies in gastrointestinal pathology suggest that colonic adenomas (precursor lesions for colonic adenocarcinoma) should not be screened routinely for LS, largely because the exact timing of somatic MMR mutations, and hence the acquisition of an MMR phenotype, in colorectal tumorigenesis is still controversial. [36][37][38][39][40][41][42][43] Unlike Pai et al, 22 we failed to find convincing evidence of histomorphologic differences across MMR-intact and MMR-deficient subclones, with 1 exception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings do not address the overall utility of screening EIN cases for LS, and, to date, there is no evidence that screening EIN for LS would be fruitfulindeed the field at large has yet to formally agree on universal screening for LS in ECs. [14][15][16][17][18][19][20] Furthermore, LS screening studies in gastrointestinal pathology suggest that colonic adenomas (precursor lesions for colonic adenocarcinoma) should not be screened routinely for LS, largely because the exact timing of somatic MMR mutations, and hence the acquisition of an MMR phenotype, in colorectal tumorigenesis is still controversial. [36][37][38][39][40][41][42][43] Unlike Pai et al, 22 we failed to find convincing evidence of histomorphologic differences across MMR-intact and MMR-deficient subclones, with 1 exception.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Given the incidence of EC in female LS patients, there has been growing interest in similarly screening all ECs for LS, with several institutions adopting universal or expanded screening protocols. [14][15][16][17][18][19][20] These universal screening protocols have brought to light various non-LS-related patterns of staining. Joost et al 21 characterized 3 distinct "heterogenous" or "subclonal" patterns of staining in colorectal carcinoma: "intraglandular" loss (retained/lost staining within glands), "clonal" loss (distinct groups of glands/whole glands without staining), and "compartmental" loss (retained/lost staining between different blocks).…”
mentioning
confidence: 99%
“…Additionally, because research has shown high sensitivity of a universal testing approach for identifying women with endometrial cancer due to Lynch syndrome, in 2016 the panel also endorses universal screening of all endometrial tumors. 30 The panel emphasizes that great care must be taken in implementing system-level universal testing to avoid loss to follow-up of patients with abnormal tests and to avoid misinterpretation of the molecular screening tests. The panel accordingly recommends that an infrastructure needs to be in place to handle the screening results.…”
Section: Definitive Testing In the Setting Of Known Lynch Syndrome Mumentioning
confidence: 99%
“…Tumors with high levels of microsatellite instability (MSI-H) or immunohistochemical loss of expression of DNA MMR proteins in the absence of MLH1 gene methylation are suggestive of Lynch Syndrome. Many recently published studies have advocated for universal screening of endometrial carcinomas with MSI and/or IHC (4,6,7). The American College of Obstetricians and Gynecologists and the Society of Gynecologic Oncology have recently issued a practice bulletin recommending that universal tissue testing as a rational approach for identifying women at risk for Lynch-associated endometrial cancer (8).…”
Section: Introductionmentioning
confidence: 99%